(untitled) (Modern education and development, 2025)
Translation plays a pivotal role in both language acquisition and the facilitation of cross-cultural communication. This thesis explores the multifaceted function of translation as a pedagogical tool in language learning and as a bridge between diverse cultures. Drawing on linguistic theories and practical classroom applications, the study investigates how translation enhances learners’ vocabulary, grammar awareness, and cultural understanding. Furthermore, the research examines translation’s impact on intercultural competence, highlighting its ability to foster empathy, reduce cultural barriers, and promote global dialogue. Through a combination of theoretical analysis and empirical evidence, this thesis argues that translation is not merely a linguistic exercise but a dynamic process that enriches language education and supports meaningful interaction between cultures. The findings underscore the need to integrate translation more consciously into language teaching methodologies and intercultural training programs.